Mesozoic mass extinctions and angiosperm radiation: does the molecular clock tell something new? - Ruban, Dmitry (Geologos, 2012)
Angiosperms evolved rapidly in the late Mesozoic. Data from the genetic-based approach called ‘molecular clock’ permit an evaluation of the radiation of flowering plants through geological time and of the possible influences of Mesozoic mass extinctions. A total of 261 divergence ages of angiosperm families are considered. The radiation of flowering plants peaked in the Albian, early Campanian, and Maastrichtian. From the three late Mesozoic mass extinctions (Jurassic/Cretaceous, Cenomanian/Turonian, and Cretaceous/Palaeogene), only the Cretaceous/Palaeogene event coincided with a significant, abrupt, and long-term decline in angiosperm radiation. If their link will be further proven, this means that global-scale environmental perturbation precluded from many innovations in the development of plants. This decline was, however, not unprecedented in the history of the angiosperms. The implication of data from the molecular clock for evolutionary reconstructions is limited, primarily because this approach deals with only extant lineages.